Análise ambiental simplificada no entorno de águas superficiais na bacia do rio Corumbataí (SP) - Borges, Maria Bernadete Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The basin of the Corumbataí river is of vital importance to over 600 thousand people, who depend on its waters for consumption. The Simplified Analisys of Environmental Impacts in the Areas Surrounding the Surface Waters of the Drainage Basin of the Corumbataí River (SP) is aimed at defining the areas which are most susceptible to degradation or already damaged and propose engineering solutions according to the environmental problems identified. Using a questionnaire to indicate possible impacts in the surroundings, I related human actions to these damage and quantified them. Having studied the basin extensively and selected 42 areas - generically identified as points and grouped as sub-basins and according to the soil usage -, I was able to identify the main environmental impacts in the basin as: sugar cane monoculture, lack of riparian forest, damaged areas due to mining, the bad state of rural roads and bridges, rubbish disposal alongside roads or directly into the river, accelerated and unplanned expansion of residential and industrial areas into the rural areas and river sources, and Rio Claro's untreated city wastewater

A bacia do rio Corumbataí é de importância vital para mais de 600 mil pessoas que dependem de suas águas para o abastecimento. A realização de análise simplificada de impactos ambientais no entorno de águas superficiais na Bacia Hidrográfica do Rio Corumbataí (SP) objetivou definir quais são as áreas mais degradadas ou susceptíveis e propor soluções de engenharia cabíveis referentes aos problemas ambientais encontrados. Foi elaborado questionário indicador de possíveis impactos no entorno que relacionou ações humanas à geração desses danos e usada uma escala de valores para quantificar a intensidade das alterações. Depois de muitos de quilômetros percorridos na bacia foram selecionadas 42 áreas, denominadas genericamente por “pontos”, agrupadas por sub-bacia e de acordo com o uso do solo. Como resultado da observação, os principais impactos ambientais na bacia são: cultura maciça de cana-de-açúcar; ausência de matas; áreas degradadas por exploração minerária; má conservação das estradas e pontes rurais; lixo depositado ao longo das estradas ou diretamente no rio; expansão acelerada e descontrolada da área residencial e industrial para a zona rural e sobre os mananciais; e o esgoto não tratado da cidade de Rio Claro
Keywords: Abastecimento de água; Impacto ambiental; Água - Qualidade; Analise ambiental; Águas superficiais; Corumbataí, Rio, Bacia (SP)